(untitled) (Journal of Psychiatrists’ Association of Nepal, 2026)
Background: Long work hours, altered schedules, and on-call periods are common practices in postgraduate medical training programs all culminating to poor sleep hygiene practices resulting in sleep loss, disruption of circadian rhythm, fatigue and excessive daytime sleepiness. Simple changes in sleeping habits can have profound impact on the overall health of postgraduate medical students ultimately leading to improved quality of patient care. Hence, the objectives of this study was to find out sleep hygiene practices and the prevalence and severity of excessive day time sleepiness among postgraduate medical students. Material and methods: A hospital based descriptive, cross-sectional study was conducted among 142 postgraduate medical students at a tertiary care center of Kathmandu for a period of six months. Enumerative sampling was used and the Ethical approval was taken from the Instituitional Review Committee. The data collected was analysed using Statistical Package for Social Sciences version 16. Results: Among the 142 participants, 116 (81.69%; 95% Confidence Interval Confidence Interval (CI): 75.30-88) had maladaptive sleep hygiene practice and excessive daytime sleepiness was present among 50 (35.21%; 95% CI: 27.40-43.10). Among those with excessive daytime sleepiness, mild severity was noticed among 13 (26.00%), moderate severity among 23 (46.00%) and severe severity among 14 (28.00%) of the participants. Conclusion: In this study majority of the participants engaged in maladaptive sleep hygiene practice and excessive daytime sleepiness was present across all three years of postgraduate training. Majority of the participants had moderate severity of excessive daytime sleepiness.